Experimental Evaluation of the Power Output and Efficiency of a Small Solar-Boosted OTEC Power Plant - Reemal D. Prasad; Muzammil Ali; Mohammed Rafiuddin Ahmed (Energies)
Ocean thermal energy is an emerging energy source that holds great promise, especially for tropical countries. Ocean thermal energy conversion (OTEC) efficiency can be improved by raising the temperature difference between the hot water and the cold water. In the work reported here, a laboratory-scale closed-cycle OTEC system was constructed and tested for power output and efficiency. A solar heating system heated the water up to 70 °C. Experiments were conducted at cold water inlet temperatures of 5 °C, 8 °C, and 11 °C. The mass flow rate of the hot water was varied, while that of the cold water was kept constant. Increasing the hot water inlet temperature from 30 °C to 70 °C while keeping the cold water inlet temperature constant at 5 °C at the highest mass flow rate of hot water increased the power output from 32.07 W to 66.68 W (107.9% increase) and the thermal efficiency from 1.96% to 4.37% (123% increase). The pressure drop across the turbine was higher for a larger temperature difference between the hot water and cold water, indicating a higher transfer of energy to the working fluid. Increasing the mass flow rate of the hot water for the increasing temperature difference between the hot water and cold water increased the power output and efficiency due to the increase in the energy transfer from the hot water to the working fluid. Experimental works on solar-boosted OTEC systems are very rare, and this work should pave the way for practical implementation.